Model Validation of a Porous Piezoelectric Energy Harvester Using Vibration Test Data - Hadi Madinei (Vibration, 2018)
In this paper, a finite element model is coupled to an homogenisation theory in order to predict the energy harvesting capabilities of a porous piezoelectric energy harvester. The harvester consists of a porous piezoelectric patch bonded to the root of a cantilever beam. The material properties of the porous piezoelectric material are estimated by the Mori–Tanaka homogenisation method, which is an analytical method that provides the material properties as a function of the porosity of the piezoelectric composite. These material properties are then used in a finite element model of the harvester that predicts the deformation and voltage output for a given base excitation of the cantilever beam, onto which the piezoelectric element is bonded. Experiments are performed to validate the numerical model, based on the fabrication and testing of several demonstrators composed of porous piezoelectric patches with different percentages of porosity bonded to an aluminium cantilever beam. The electrical load is simulated using a resistor and the voltage across the resistor is measured to estimate the energy generated. The beam is excited in a range of frequencies close to the first and second modes using base excitation. The effects of the porosity and the assumptions made for homogenisation are discussed.